Detection of anomalous Hall voltages in ultrahigh-mobility two-dimensional hole gases generated by optical spin orientation - Vasyukov, D.A.; Plaut, A.S.; Henini, M.; Pfeiffer, L.N.; West, K.W.; Nicoll, C.A.; Farrer, I.; Ritchie, D.A. (American Physical Society, 2015)
By combining optical spin orientation and an externally applied longitudinal electric field, transverse charge accumulation has been detected in very high-mobility two-dimensional hole gases by measuring the transverse voltage drop across simple Hall devices. Our results indicate intrinsic band-structure (rather than extrinsic skew scattering) derived spin-orbit coupling as the underlying mechanism of this spin-polarized transport effect.